Gender Stereotype and the Voting Behavior of the Balinese Society in the 2014 Legislative Election - Apriani, Kadek Dwita; Raffiudin, Riaty (Talenta Publisher, 2019)
This research explains the relationships between gender stereotypes that live inside patriarchal culture among Balinese with voting behaviour of female candidates in the 2014 legislative election. Using quantitative method, the number of the samples are 800 which are proportionally spread in all Bali regencies and cities. The margin of error of this research is 3% at 95% confidence level. The sampling technique used is multi stage random sampling. The research findings suggest that in the 2014 legislative election, only 4% of the Balinese respondents voted for female candidates. This is due to the gender stereotyping factor, where there are very few issues or policies that are considered more capable of being resolved by female politicians. Almost all the issues that become problems in the daily life of the Balinese people are considered by the respondents to be better resolved by male politician